Literatura bez granic? Media digitalne i ich wpływ na status sztuki słowa - Winiecka, Elżbieta (Przestrzenie Teorii, 2019)
The article concerns electronic literature and its place at the interface of traditional literature, technology and visual arts. This new genre of literature, associated with the development of digital media, shows that the boundaries of classical arts and disciplines in scientific research are blurring. This new phenomena require a new, transdisciplinary approach, combining literary and humanist competences with programming knowledge. The author presents a new literary phenomenon and indicates that literariness is a category which is more functional than literature in the case of studying e-literary. Literariness applies not only to literary works but also to other arts and phenomena in which it is the dominant feature of the work. This is exactly what happens in the case of electronic literature. It remains in the field of creativity in which the role of the word is the most important. At the same time, programming skills are required from the artist and the researcher, which do not fall within the scope of classical humanities. The author indicates that e-literary creativity is an area that opens up new perspectives for literary studies. It also sets new requirements for literary researchers.